Developing the content of a brief universal acceptance and commitment therapy (ACT) programme for secondary school pupils: InTER-ACT. (2nd January 2023) - Samuel, Victoria; Constable, Chloe; Harris, Emma; Channon, Susan
ABSTRACT: Mental health difficulties often start in childhood and the number of young people experiencing mental health difficulties is rising, particularly since the Covid-19 pandemic. School-based programmes have been identified as an effective way to provide support for young people and present an opportunity to offer universal programmes, which can increase equity of access, facilitate resilience and reduce stigma. Whilst there is an emerging evidence of the benefits of preventive mental health programmes delivered in schools, there is a need for more robust evidence and methodological rigour in the development and descriptions of these programmes. Acceptance and Commitment Therapy (ACT) is one approach that may be appropriate as a framework for preventing and reducing mental health difficulties in schools. This paper describes the content development of a UK-based universal school programme using ACT: the In-school Training in Emotional Resilience (InTER-ACT) programme. It describes the steps taken across the stages of content development, from planning the programme, delivering the programme in a school, receiving feedback and integrating the subsequent revisions. The final version of the programme, including summaries of session content, is provided. Consistent with an ACT ethos, the personal values of the researchers, and the influence of these on the programme are discussed, providing a novel integration of methodical detail and authentic, reflective practice. This article provides a transparent and detailed overview of the iterative processes involved in developing the content of an evidence-based pastoral care programme in a way that is systematic, rigorous and responsive to teacher and pupil feedback.